PENGARUH MODEL PEMBELAJARAN MORDISCVEIN TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS V SEKOLAH DASAR - Pohan, Ade Hermansyah; Ginting, Susanna; Arfika, Nurul; Rajagukguk, Suryana (JS (JURNAL SEKOLAH), 2023)
Abstract: The Effectiveness of Mordiscvein Learning Model in Improving Mathematics Learning Outcomes of Grade V Elementary School Students. This study aimed to explore the effectiveness of the Mordiscvein learning model in improving mathematics learning outcomes of grade V primary school students. This study was conducted at SDN 060959, Medan Belawan sub-district, with grade V students as the study subjects. It was conducted over a period of approximately 4 weeks. Data were collected through tests, observations, and questionnaires. Data were analysed from learning outcomes, student activities, and student responses to the Mordiscvein learning model. The test data was analysed using paired t-test and N-Gain analysis. The results of the study explain that the Mordiscvein learning model has a high level of effectiveness, this is shown that the Mordiscvein learning model can significantly improve student learning outcomes from the analysis of initial and final scores, as evidenced by the N-Gain results which get a percentage of 85% with very effective achievement. Keywords: Learning Outcomes, Maths, Mordiscvein Learning Model. Abstrak: Keefektifan Model Pembelajaran Mordiscvein dalam Meningkatkan Hasil Belajar Matematika Siswa Kelas V Sekolah Dasar. Kajian ini bermaksud mengeksplorasi keefektifan model pembelajaran Mordiscvein dalam meningkatkan hasil belajar matematika siswa kelas V sekolah dasar. Kajian ini dilaksanakan di SDN 060959 Kec. Medan Belawan, dengan siswa kelas V sebagai subyek kajian. Yang dilakukan dalam kurun waktu kurang lebih 4 minggu. Data dikumpulkan melalui tes, observasi, dan kuesioner. Data analisis dari hasil belajar, aktivitas siswa, dan respon siswa terhadap model pembelajaran Mordiscvein. Data hasil tes dianalisis dengan menggunakan uji-t berpasangan dan analisis N-Gain. Hasil kajian memaparkan bahwa model pembelajaran Mordiscvein tingkat keefektifan yang tinggi, hal ini ditunjukkan bahwa model pembelajaran Mordiscvein dapat meningkatkan hasil belajar siswa secara signifikan dari hasil analisis nilai awal dan nilai akhir, terbukti dari hasil N-Gain yaitu mendapatkan persentase 85% dengan capaian sangat efektif.Kata Kunci : Hasil Belajar, Matematika, Model Pembelajaran Mordiscvein